2016
DOI: 10.21037/jtd.2016.03.08
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory distress syndrome caused by Mycoplasma pneumoniae without elevated pulmonary vascular permeability: a case report

Abstract: Sporadic patients with acute respiratory distress syndrome (ARDS) caused by Mycoplasma pneumoniae have been reported. However, knowledge about the pathophysiology and pharmacological treatment of this condition is insufficient. Moreover, the pulmonary vascular permeability in ARDS related to M. pneumoniae infection has not been reported. We report a case of ARDS caused by Mycoplasma pneumoniae without elevated pulmonary vascular permeability, which was successfully treated using low-dose short-term hydrocortis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Prolonged or inappropriate use of corticosteroids may cause excess downregulation of cell-medicated immunity and result in immunosuppression, making individuals more susceptible to more severe M. pneumoniae infection or opportunistic infections. A recent case report revealed that M. pneumoniae associated ARDS had no elevated pulmonary vascular permeability, and was successfully treated using low-dose short-term hydrocortisone, suggesting that pulmonary infiltration in ARDS caused by M. pneumoniae does not match the criteria of permeability edema observed in typical ARDS [35]. Therefore, careful consideration is required when deciding whether to use high dose corticosteroid in the future cases similar to ours.…”
Section: Discussionmentioning
confidence: 65%
“…Prolonged or inappropriate use of corticosteroids may cause excess downregulation of cell-medicated immunity and result in immunosuppression, making individuals more susceptible to more severe M. pneumoniae infection or opportunistic infections. A recent case report revealed that M. pneumoniae associated ARDS had no elevated pulmonary vascular permeability, and was successfully treated using low-dose short-term hydrocortisone, suggesting that pulmonary infiltration in ARDS caused by M. pneumoniae does not match the criteria of permeability edema observed in typical ARDS [35]. Therefore, careful consideration is required when deciding whether to use high dose corticosteroid in the future cases similar to ours.…”
Section: Discussionmentioning
confidence: 65%
“…Respiratory infections caused by M. pneumoniae are also associated with a wide array of extrapulmonary manifestations such as meningoencephalitis, myocarditis, nephritis, atherosclerosis and mucocutaneous eruptions, etc. [ 13 , 14 , 15 , 16 , 17 ]. More importantly, M. pneumoniae induces mucocutaneous diseases include Stevens-Johnson syndrome and M. pneumoniae -associated mucositis.…”
Section: Introductionmentioning
confidence: 99%
“…The airway infections by M. pneumoniae are also connected with several extra-pulmonary complications like nephritis, myocarditis, meningoencephalitis, mucocutaneous disruptions, and atherosclerosis. [11,12] The majority of M. pneumoniae infected pneumonia patients recovered after treatments with tetracycline and macrolides. Although in recent times, the elevating use of antibiotics, the antibiotic-resistant M. pneumoniae strains have emerged and the refractory pneumonia incidences have increased.…”
Section: Introductionmentioning
confidence: 99%